1999
DOI: 10.1177/109114219902700504
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrage, Speculation, and Public Policy Toward Ticket Scalping

Abstract: PUBLIC FINANCE REVIEWTicket scalping is typically analyzed from the point of view of the demanders of the product. The question of why a profit-maximizing producer would let someone purchase its product for speculation or arbitrage has typically been ignored in the literature. There are at least three reasons why a profit-maximizing firm might permit purchase of its product for resale. One reason is that uncertainty and risk aversion on the part of the firm provides an opportunity for speculation in the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Swofford [1999] describes a one-period model in which scalpers act as middlemen and exploit selling opportunities that the producer cannot due to differences in risk preferences, costs, or demand. In Swofford's model, scalpers sell tickets that would otherwise go unsold, and in this way may actually increase profits for the producer.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Swofford [1999] describes a one-period model in which scalpers act as middlemen and exploit selling opportunities that the producer cannot due to differences in risk preferences, costs, or demand. In Swofford's model, scalpers sell tickets that would otherwise go unsold, and in this way may actually increase profits for the producer.…”
Section: Related Literaturementioning
confidence: 99%
“…On the other hand, if scalpers raise the profits of producers by acting as "insurance," we would expect to see increased entry and number of productions in markets where scalping is legal without restrictions. Finally, if scalpers simply extract profits that producers would not be able to obtain otherwise, then we would expect to see increased consumption (tickets sold) and no effect on the number of productions; for any given performance, scalpers would be selling tickets that would be left unsold in their absence [Swofford 1999]. Table 5 reports the results of our OLS regressions.…”
Section: Productionmentioning
confidence: 99%
“…However, it has been shown that, for example, ticket prices in the American baseball league are determined by a monopolistic profit maximizing strategy (Alexander, 2001). Swafford (1999) shows that low prices might be optimal in a situation with demand uncertainty. Although uncertainty might always play a role in real world markets, it is beyond doubt that many entertainment events where underpricing is observed are expected to sell out at these prices.…”
Section: Related Literaturementioning
confidence: 99%
“…Swofford (1999) considers price discrimination and explains why different views toward risk, different cost functions, or different abilities to price discriminate may make scalping profitable. Happel and Jennings (1995) discuss antiscalping laws without using a formal model.…”
Section: Introductionmentioning
confidence: 99%